PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE TOKOPEDIA DENGAN KEPERCAYAAN SEBAGAI VARIABEL MEDIASI - Ulfa Fionita Sakka; Beni Suhendra Winarso (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Responding to the uncertain economic conditions caused by the pandemic, MSMEs remain a solution to improve the economy by using a different marketing system using the digital world. Marketing strategies using the digital world can be done by utilizing existing marketplaces to make sales online. Many factors influence a person in the use of the market in shopping for merchandise, including promotions and prices. The sample in this study was 118 Tokopedia marketplace consumers. The data collection technique in this study used questionnaires that were shared online. The analysis tool in this study uses the Multiple Regression Test plus the Sobel Test. The results of the study partially show that promotion and price have an influence on purchasing decisions on the Tokopedia marketplace, while trust can mediate the influence of promotion and price on purchasing decisions on the Tokopedia marketplace. Keywords: Purchase Decision, Promotion, Price, and Trust.